Quality of Life, Perceived Stigma, and Depression among People Living with HIV/AIDS - Stefanovic, Claudio; Buntoro, Ika Febianti; Iswaningsih, Iswaningsih; Legoh, Dickson Alan (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: The intersecting challenges of a growing population of people living with HIV/AIDS (PLWHA), efforts to improve their quality of life (QoL), and the ongoing persistence of stigma contribute to an increasing incidence of depression among PLWHA. Existing research presents conflicting evidence and seldom addresses the interplay between QoL, perceived stigma, and levels of depression. This study aims to fill that gap by examining the effects of QoL and perceived stigma on the depression levels of PLWHA.Method: A cross-sectional study involving 97 PLWHA was conducted. The face-to-face measures included the WHOQOL-BREF, the Modified Berger HIV Stigma Scale, and Hamilton Depression Rating Scale (HDRS). An ordinal logistic regression model was employed to identify associations between QoL, perceived stigma, depression, and other potential predictor variables.Result: Among the 97 PLWHA, the majority were male (55.7%), belonged to the early adult age group (39.2%), and had completed senior high school (53.6%). The QoL results indicated that 47.4% reported good QoL, while 52.6% reported poor QoL. Regarding perceived stigma, 50.5% felt not stigmatized, whereas 49.5% felt stigmatized. The levels of depression were categorized as follows: normal/not depressed (68%), mildly depressed (11.3%), moderately depressed (8.2%), severely depressed (6.2%), and very severely depressed (6.2%). This research underscores that QoL serves as a protective factor against depression and mitigates the negative effects of stigma on mental health, highlighting the urgent need for targeted interventions and holistic approaches.